Adaptation of a dynamic in vitro model with real-time determination of butyrylcholinesterase activity in the presence of cyclosarin and an oxime. Issue 1 (February 2015) - Worek, Franz; Horn, Gabriele; Wille, Timo; Thiermann, Horst
Highlights We adopted an in vitro model for the continuous real-time determination of human BChE activity. The interactions of human BChE, cyclosarin and the oxime HLö 7 were investigated. This model allows the investigation of BChE as a 'pseudo-catalytic' scavenger.